2019
DOI: 10.3390/v11010032
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of the Role of Ecologically-Relevant Hosts and Vectors in Japanese Encephalitis Virus Genotype Displacement

Abstract: Japanese encephalitis virus (JEV) is a flavivirus that is maintained via transmission between Culex spp. mosquitoes and water birds across a large swath of southern Asia and northern Australia. Currently JEV is the leading cause of vaccine-preventable encephalitis in humans in Asia. Five genotypes of JEV (G-I–G-V) have been responsible for historical and current outbreaks in endemic regions, and G-I and G-III co-circulate throughout Southern Asia. While G-III has historically been the dominant genotype worldwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 53 publications
2
30
0
Order By: Relevance
“…In addition, several experimental studies showed that domestic birds can be infected with JEV (5,14,15) and might even act as JEV reservoirs (39,40). However, it is controversially discussed if they develop a sufficient viremia to infect mosquitoes (14,(41)(42)(43). In our study, ducks were more likely to be seropositive when they are 10 months or older than chickens (87.1% of ducks seropositive compared to 33.3% of chickens of that age).…”
Section: Discussionmentioning
confidence: 60%
“…In addition, several experimental studies showed that domestic birds can be infected with JEV (5,14,15) and might even act as JEV reservoirs (39,40). However, it is controversially discussed if they develop a sufficient viremia to infect mosquitoes (14,(41)(42)(43). In our study, ducks were more likely to be seropositive when they are 10 months or older than chickens (87.1% of ducks seropositive compared to 33.3% of chickens of that age).…”
Section: Discussionmentioning
confidence: 60%
“…Depending on the study, GI was shown to replicate more efficiently in pig, avian, and mosquito cells than GIII (10,47,48). Genotype I had a higher infection rate and shorter extrinsic incubation period than GIII during in vivo studies using C. quinquefasciatus (12). Whereas, these studies help to explain how GI might have displaced the previous genotype, other host and environmental factors, such as effects of immunity of a population to the different genotypes, changes in farming, and animal husbandry practices, and changes in migratory patterns of birds, may have also contributed to the emergence of GI.…”
Section: Jev Genomics and Phylogenymentioning
confidence: 99%
“…Future genotype displacement or genetic modifications can compromise current cross-protection, and in turn threaten vaccine effectiveness, current immunization and other public health programs (12). Other challenges associated with emergence or reemergence of JEV genotypes could include changes in transmission paths, disease burden, or host demographics (11,84).…”
Section: Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Vietnam is located in the tropics of Southeast Asia, and several mosquito-borne diseases are endemic, including Japanese encephalitis [ 1 ], dengue fever [ 2 ], and Zika [ 3 ]. Culex species are considered to be important vectors of Japanese encephalitis virus (JEV), including Culex quinquefasciatus Say (Diptera: Culicidae) [ 4 ], but other mosquito genera may also serve as competent vectors of the virus [ 5 , 6 ]. Dengue fever is hyperendemic to Vietnam with all four serotypes of the virus in circulation, resulting in periodic acute epidemics of both dengue fever and dengue hemorrhagic fever [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%